London bus dispute, 1958 (London, 1958)
1958 1951-1960 "London bus dispute, 1958" [BW0039], 1958, Trades Union Congress Front page of the TUC magazine, Labour, during the London bus strike, which saw the complete withdrawal of all Central and Country areas buses from May 5 to June 20, 1958. London Transport had offered a pay increase only to Central London bus services and nothing to Country and Green Line services. 50,000 bus workers came out, but although some concessions were eventually made, the strike was seen as unsuccessful and the Transport and General Workers' Union suffered severe financial losses. A strike-breaking organisation, calling itself "The People's League for the Defence of Freedom" obtained permission to run a few bus services in and around the capital.